Theoretical Investigation on Structural and Electronic Properties of InN Growth on Ce-Stabilized Zirconia (111) Substrates - Yao Guo; Taixuan Jia; Chengbo Li; Yongsheng Niu; Shaogang Hou; Shuanjiang Liu (Advances in Condensed Matter Physics)
The structural and electronic properties of InN on Ce-stabilized zirconia (CeSZ) (111) substrates are investigated using first-principles calculations based on density functional theory with GGA + U method. Surface energy calculations indicate that the structure of Ce-segregated surface is more energetically stable than that of Ce-segregation-free surface. Adsorption energies of indium and nitrogen atoms on both Ce-segregated and Ce-segregation-free CeSZ (111) surfaces at the initial growth stage have been studied. The results suggest that the first layer of InN films consists of a nitrogen layer, which leads to epitaxial relationships between InN (0001) // CeSZ (111) and InN [112¯0] // CeSZ [11¯0]. In addition, density of states (DOS) analysis revealed that the hybridization effect plays a crucial role in determining the interface structure for the growth of InN on CeSZ (111) surfaces. Furthermore, adsorption energies of indium atoms on the nitrogen layer have also been evaluated in order to investigate the lattice polarity determination for InN films. It was found that an indium atom preferentially adsorbs at the center of three nitrogen atoms stacked on the CeSZ substrate, which results in the formation of In-polarity InN.